Enhancing English Language Vocabulary Learning among Indigenous Learners through Google Translate - Kai, Ting Fang; Hua, Tan Kim (Journal of Education and e-Learning Research, 2021)
The emergence of new technologies has brought massive changes to teaching and learning processes. In recent years, mobile phones have evolved into effective teaching tools; when used practically, they could improve learning outcomes. The potential of mobile phones as a learning platform has led to a proliferation of research into their effectiveness. This paper aims to examine the effectiveness of the Google Translate mobile application (hereinafter “app”) in improving indigenous learners’ English language vocabulary. Fifteen Iban participants with low English language proficiency from rural schools were chosen through purposive sampling. The data were collected by comparing scores in the pre-test and post-test. In addition, the data were triangulated through structured interviews. Key findings indicated that almost all participants achieved high scores in the post-test. The interviews also revealed that all participants affirmed that Google Translate supports their English language proficiency, and only one participant was unsure of its effectiveness. Thus, the findings of this study imply that Google Translate could be an effective teaching tool to enhance learners’ English language vocabulary. Future research could examine the effectiveness of the app in teaching vocabulary in different contexts.